ChemInform Abstract: Copper‐Catalyzed Three‐Component Reaction for Regioselective Aryl‐ and Heteroarylselenation of Indoles Using Selenium Powder. Issue 41 (September 2016) - Luo, Dongping; Wu, Ge; Yang, Hang; Liu, Miaochang; Gao, Wenxia; Huang, Xiaobo; Chen, Jiuxi; Wu, Huayue
Abstract: A copper‐catalyzed C3 aryl‐ and heteroarylselenation of indoles employing selenium powder is developed, which is also elaborated in an intramolecular phenylselenation of a (hetero) aryl C—H bond to construct a motif of benzoselenopheno[3, 2‐b]indole.